2009
DOI: 10.1002/pssb.200844362
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and XPS investigations of Cu2+‐doped ZnS quantum dots capped with polyvinylpyrrolidone

Abstract: Cu2þ -doped ZnS quantum dots were synthesized by a chemical precipitation method in water/ethanol solution. The quantum dots obtained were characterized by X-ray diffraction, transmission electron microscopy and spectroscopy techniques including X-ray photoelectron spectroscopy. ] ¼ 1:1. For powders, only the green emission is the main luminescence centre, and the integrated intensity in the blue emission region of sample 1 is stronger than that of sample 2. Compared with the spectrum of CuS powders, the X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…For Hg-containing samples, CdSe/ZnS-HgS and InP/ZnS-HgS, the Hg 4 d area between 350 and 385 eV was used rather than the more conventional Hg 4 f or Hg 5 d area due to masking elements, particularly Si 2 p masking of Hg 4 f , since QD samples were mounted on glass prior to analysis ( Figure 3 ). [44][45][46][47] To gauge the location of the Hg within the doped samples, ToF-SIMS analysis was performed on a sample of bulk CdSe coated using the shelling protocol with a 1:1 ratio of mercury(II) diethyldithiocarbamate and zinc(II) diethyldithiocarbamate. This showed an increase in the Cd concentration with increasing etch time, indicating cadmium would be present in the QD core only, in contrast to that seen in the CdS-ZnS shelling in 1a .…”
Section: Hg Addition (2a 2b)supporting
confidence: 81%
See 1 more Smart Citation
“…For Hg-containing samples, CdSe/ZnS-HgS and InP/ZnS-HgS, the Hg 4 d area between 350 and 385 eV was used rather than the more conventional Hg 4 f or Hg 5 d area due to masking elements, particularly Si 2 p masking of Hg 4 f , since QD samples were mounted on glass prior to analysis ( Figure 3 ). [44][45][46][47] To gauge the location of the Hg within the doped samples, ToF-SIMS analysis was performed on a sample of bulk CdSe coated using the shelling protocol with a 1:1 ratio of mercury(II) diethyldithiocarbamate and zinc(II) diethyldithiocarbamate. This showed an increase in the Cd concentration with increasing etch time, indicating cadmium would be present in the QD core only, in contrast to that seen in the CdS-ZnS shelling in 1a .…”
Section: Hg Addition (2a 2b)supporting
confidence: 81%
“…Hg containing samples used the Hg4d area between 350 and 385 eV rather than the more conventional Hg4f or Hg5d due to masking elements, particularly Si2p masking of Hg4f, as all QD samples for analysis were mounted on glass prior to analysis (figure 3). [39][40][41][42] [ Figure 3]…”
Section: Hg Doping (2a 2b)mentioning
confidence: 99%
“…It has been shown that doping can alter the band structure by creating local quantum states that affect their (opto)electronic properties. Many transition metals have been introduced in QDs, such as Mn, [69] Cr, [70] Cu, [71] and Co [72] . A major drawback regarding their fabrication is the difficulty of controlling their size and distribution.…”
Section: Fullerene–0d Nanomaterials Hybridsmentioning
confidence: 99%
“…Several reports have utilized vapor-phase methods to prepare QDs.T he process begins by growing layers atom-by-atom, thus the QD growth can occur without patterning.The growth takes place in different ways:epitaxial growth, [67] formation of as mooth layer followed by nucleation and growth of small islands, [68] or the growth of small islands directly onto the substrate. [51] One important aspect that can be tuned during QD synthesis is the introduction of small quantities of other materials.I th as been shown that doping can alter the band structure by creating local quantum states that affect their (opto)electronic properties.M any transition metals have been introduced in QDs,s uch as Mn, [69] Cr, [70] Cu, [71] and Co. [72] Am ajor drawback regarding their fabrication is the difficulty of controlling their size and distribution. Acommon solution is the utilization of capping-agents-like organic ligands,s uch as oleic acid or oleylamine.…”
Section: Fullerene-0d Nanomaterials Hybridsmentioning
confidence: 99%
“…However, in view of recent environmental regulation, the intrinsic toxicity of cadmium brings a doubt on the future applicability of the cadmium compounds despite of their great optical and electrical properties. Thus, several Cd-free alternative materials have been proposed including III-V semiconductor nanocrystals and transition-metaldoped ZnS and ZnSe QDs [10][11][12].…”
Section: Introductionmentioning
confidence: 99%